Jebakan Toxic Positivity Berlabel Ibadah: Dekonstruksi Makna Amanah dalam Manajemen Kesejahteraan Mental Guru Madrasah - Samsul Hadi; Tarekah Hasanah; Muhammad Akmansyah (Lentera: Jurnal Ilmiah Kependidikan, 2026)
The mental health of madrasah teachers is a crucial issue often overlooked behind narratives of piety and devotion. This study aims to uncover the phenomenon of toxic positivity labeled as worship and deconstruct the meaning of "amanah" (trustworthiness) often misused in human resource management in madrasahs. Using a library research method with a Critical Discourse Analysis (CDA) approach, this study examines literature on psychology, Islamic education management, and religious texts to identify how religious jargon is used to suppress valid teacher complaints regarding workload and well-being. The findings indicate that toxic positivity in the madrasah environment often manipulates the concepts of "patience" and "sincerity" to normalize labor exploitation, while the meaning of "amanah" has been hegemonized into a one-way obligation from teachers to institutions without fair reciprocity. Through theological deconstruction, this study reformulates the concept of amanah into "bilateral amanah" which integrates the principles of justice ('adl) and self-preservation (hifz al-nafs). This reconstruction offers a new management paradigm where emotional validation and setting work boundaries are viewed as part of worship and an absolute prerequisite for sustainable quality education.